SEASONAL VARIABILITY OF PULSE WAVE VELOCITY IS ASSOCIATED WITH CARDIOVASCULAR OUTCOMES IN HYPERTENSIVE PATIENTS. (April 2021) - Yana, Koshelyaevskaya; Smirnova, Marina; Gorbunov, Vladimir; Deev, Alexander; Volkov, Dmitry; Furman, Nikolay; Dolotovskaya, Polina
Abstract : Objective: The seasonal changes of blood pressure in hypertensive patients have been investigated and attracted an increasing scientific interest during the past years, but seasonal changes of pulse wave velocity (PW) in hypertensive patients have not been studied. And it is unclear whether PW variations are related to cardiovascular risk. The aim of the study was the examination of prognostic value of individual variability of PW in 24-hour, daytime and nighttime periods of hypertensive patients from two regions of the Russia (Ivanovo and Saratov). Design and method: Patients aged 40–79 years who visited ambulatory clinics for various reasons we. All participants provided written informed consent. The ambulatory blood pressure monitoring (ABPM) was performed with the BPLab device, twice in all patients: in winter (December-February 2012–2014) and in summer (June-August 2012–2014). The interval between ABPMs was 6 months ± 7 days. The selection criteria for ABPM records were: duration > = 23.5 hours, absence of data gaps >1 hour, and > = 56 readings per 24 hours. We analyzed the individual PW in 24-hour, daytime and nighttime differences in each patient. The participants were followed up until October 31-st 2019 (mean follow-up 6.4 ± 0.4 years). The complex endpoint included death (from any reasons), stroke, myocardial infarction, transient ischemic attack, angina pectoris, and development of heart failure. The preliminary analyses included ANOVA and descriptive statistics. Results: In total, 770 patients completed both visits. The outcome information was available in 528 patients: 335 from Ivanovo and 193 from Saratov (mean age 55 ± 10 years, 220 men). The endpoints were registered in 50 patients. We found the mean winter-summer PW difference in the group of patients with cardiovascular outcomes. In contrast, this difference was positive in the other group (see Table1). Figure. No caption available. Conclusions: The inverse seasonal PW variability, which could reflect the abnormal biological response to outside temperature, may be associated with a higher risk of cardiovascular events, compared to patients with standard PW variability (PW is higher in winter, than in summer). Our data demonstrate the preliminary argument in favor of additional ambulatory BP and PW control. The problem of seasonal PW variability is needed further studying.